Building trust in American hospital-community development projects: a scoping review - Samantha Nandyal; David Strawhun; Hannah Stephen; Ashley Banks; Daniel Skinner (Greater Baltimore Medical Center, 2021)
Although it has become increasingly common for hospitals to engage in development projects aimed at improving the social determinants of health in surrounding communities, scholarly literature examining the establishment of trust between hospitals and communities is sparse. Because of an extensive and complex history of abuse suffered by marginalized populations at the hands of medical institutions, trust building is critical to the pursuit of equitable health outcomes in these communities. A scoping review was conducted to assess the current base of knowledge for building trust between hospital systems and community members. The review identified only 13 relevant articles addressing this topic, centered on six key themes: with whom to form partnerships; how to form partnerships; conceptualizing and defining trust; questions about investment and hiring; effective communication with communities; and, understanding communities.